Performance of the Tunisian 'Maltaise Demi Sanguine' Sweet Orange Inoculated with Citrus Exocortis Viroid (CEVd) and Cachexia Viroid (CVIIb) on Eight Rootstocks - Najar, Asma; Homri, Najoua; Bouhlel, Rym; Ben Mimoun, Mehdi; Durán-Vila, Núria (2017)
The performance of 'Maltaise demi-sanguine' sweet orange infected with Citrus exocortis viroid (CEVd) and Hop stunt viroid (HSVd, Variant CVIIb) was evaluated on eight different rootstocks (sour orange, 'Carrizo' citrange, volkamer lemon, 'Cleopatra' mandarin, 'Swingle' citrumelo, 'Rangpur' lime, alemow and trifoliate orange) at the INRAT station in El Gobba, Cap Bon region, Tunisia. The trees were planted in 2005 and fruit production and fruit quality and size were evaluated every year since 2007. For non-inoculated trees, the trunk circumference was larger for plants grown on citrumelo, volkamer lemon and 'Carrizo' citrange than for those grown on sour orange. Trees on volkamer lemon also had a larger canopy volume. Infection with HSVd-CVIIb caused severe stunting and low production on trees grafted on alemow, and to a lesser extent reduced trunk diameter and production of trees on 'Swingle' citrumelo, whereas inoculation with CEVd or HSVd had little effect on the growth and yield of trees propagated on the other rootstocks. The only effect of HSV-CVIIb infection on fruit quality consisted of increased juice weight in plants propagated on 'Rangpur' lime and acidity in plants on volkamer lemon and decreased total soluble solids in plants on sour orange.